Formulation of Accountability of Islamic University in Islamic Values Perspective - Ari Dewi Cahyati; Nurma Risa; Nizarul Alim; Prasetyono Prasetyono (Global Review of Islamic Economics and Business, 2019)
Islamic University as a sharia non-profit institution needs to implement accountability to stakeholders. The purpose of this study is to formulate accountability models in the perspective of Islamic values at Islamic University 45. This study uses a qualitative paradigm approach. Data collection techniques were carried out by in depth interviews and Focus Group Discussion (FGD). Informants of this study were university stakeholders consisting of: Lecturers, Head of Departments, Deans, vice chancellor, Chancellors, Foundations, Graduates, Students, Government (Grant providers) and surrounding communities. The results of the study is divided Islamic accountability in 2 (two) dimensions, and Abd Allah, which Khalifatulfiilardis consisted of legal accountability, economic accountability, social accountability to society and the environment, and accountability to Allah.